2014
DOI: 10.3111/13696998.2014.975233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, treatment patterns, and economic burden in patients treated for neuroendocrine tumors in the United States: a retrospective cohort study

Abstract: Substantial clinical and economic burden exists among individuals with NET treated with medical or surgical therapies. Future research should investigate this treated sub-population considering a longer follow-up due to slow disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…This adds to the already considerable financial burden associated with surgical or medical therapy for NET management. 6 A retrospective study reported that monthly total health care costs of NET patients in the United States who were treated with medical therapy increased from $5629.70 in the 6 months preceding the diagnosis to $9093.30 in the 12 months following (an increase of more than 60%). For those receiving surgical therapy, the costs increased from $2547.90 to $8810.40 in the 6 months before and 12 months after the diagnosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This adds to the already considerable financial burden associated with surgical or medical therapy for NET management. 6 A retrospective study reported that monthly total health care costs of NET patients in the United States who were treated with medical therapy increased from $5629.70 in the 6 months preceding the diagnosis to $9093.30 in the 12 months following (an increase of more than 60%). For those receiving surgical therapy, the costs increased from $2547.90 to $8810.40 in the 6 months before and 12 months after the diagnosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For those receiving surgical therapy, the costs increased from $2547.90 to $8810.40 in the 6 months before and 12 months after the diagnosis, respectively. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to characterizing the various treatments, dose data for octreotide, the most common SSA treatment in this study, were analyzed, and the analysis showed most octreotide administrations were given at the standard dose of 30 mg/4 weeks for CS treatment. Furthermore, whereas prior studies on resource use for patients with NET have focused on all‐cause use , this study adds to the literature by showing lung NET‐related resource use following advanced lung NET diagnosis.…”
Section: Discussionmentioning
confidence: 83%